Effect of HGF on the apoptosis of rat corpus cavernosum smooth muscle cells induced by TGFβ1. (11th November 2014) - Liu, T.; Peng, Y.‐F.; Jia, C.; Yang, B.‐H.; Tao, X.; Fang, X.; Zhong, W.
Summary Corpus cavernosum smooth muscle cells (CCSMCs) are important functional cells for penile erection. We evaluated the effect of transforming growth factor β1 (TGFβ1) and hepatocyte growth factor (HGF) on the viability and apoptosis of CCSMCs in vitro. CCSMCs from healthy male Sprague Dawley rats were randomly divided into four groups: a negative control group, a TGFβ1 group, a HGF group and a HGF+ TGFβ1 group. Differences in cell viability and apoptosis among groups were observed by 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5 diphenyl tetrazolium bromide (MTT) assay and flow cytometry. Western blot was used to detect the change of apoptosis‐related proteins. The level of reactive oxygen species (ROS) was detected by colorimetry. In the TGFβ1 group, the MTT values were obviously decreased at 12 h, 24 h, 48 h―0.320, 0.383 and 0.432 respectively. However, compared with the normal group, the apoptosis index was markedly increased, reaching 26.86% at the 48‐h time point. After TGFβ1 treatment, the levels of cleaved caspase‐3 and p‐Smad2 were increased in the cells, but the levels of Bcl‐xL, Bcl‐2 and p‐Akt were significantly lower. However, HGF co‐treatment partially reversed these changes and could decrease the intracellular ROS level while increasing the Akt phosphorylation level. These results indicate that TGFβ1 might induce apoptosis of CCSMCs in vitro and that HGF could interfere with the above process through downregulation of apoptosis signalling and oxidative stress reaction.